Islamic Business and Performance Management: The Maslahah-Based Performance Management System - Firdaus, Achmad (Islamic Business and Management Series, 2023)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Foreword by Dzulkifli Abdul Razak -- Preface -- Acknowledgements -- PART I: Organization Requires done Maslahah -- 1. Islamic Economic System: Maslahah in a Muslim State Economy -- 2. Falah as Organizational Goal -- 3. Maslahah as the Intermediary Organizational Objective -- 4. Individual Maslahah Fulfilment Efforts -- PART II: Maslahah as a Basis for the Organizational Performance System -- 5. The Measures of Organizational Performance and Fulfilment Efforts -- 6. Maslahah and Orientations -- 7. Customer Orientation and Preservation of Customer Relationship -- PART III: Managing Maslahah-Based Organizational Performance System -- 8. PDCA Cycle of MaP Performance System -- 9. Performance Planning -- 10. Performance Implementation -- 11. Performance Evaluation -- 12. Performance Action -- PART IV: Application of Maslahah-Based Performance System -- 13. Maslahah Performa Building -- 14. Case Study -- 15. Conclusion -- Bibliography -- Glossary -- Index.